Construction of Concrete Dams in Areas with Subzero Mean Annual Temperature (Stroitel'Stvo Betonnykh Plotin v Raionakh s Otritsatel'noi Srednegodovoi Temperaturoi) - Mal'tsov, K. A.; Plyam, Sh. N.; Kudoyarov, L. I. (1976)
Building concrete hydraulic engineering structures in regions with severe climatic conditions characterized by a subzero average yearly temperature raises a number of problems which do not occur when dams are constructed in regions with a moderate or warm climate. These problems arise because of the complete freezing of a considerable amount of the embankment of a concrete dam during the operational period on the one hand, and the change in the thermomechanical properties of the concrete (coefficient of linear expansion, strength, modulus of elasticity, etc.), on the other hand. This report addresses those problems. Trans. of Vsesoiuznyi nauchnoissledovatel'skii institut gidrotekhniki, Izvestiia (USSR) v101 p133-138 1973.